A 1 Ma sea surface temperature record from the North Atlantic and its implications for the early human occupation of Britain. Issue 2 (17th August 2018) - Candy, Ian; Alonso-Garcia, Montserrat
Abstract: The British Quaternary sequence has an exceptionally rich record of Palaeolithic archaeology up to 1 Ma. In this study, we reinvestigate foraminifera-based sea surface temperature (SST) reconstructions from the two marine core records (Ocean Drilling Program Site 980 and M23414) that are most relevant to the climatic history of the British Isles, consequently allowing the evolution of SST over the past 1 Ma to be studied. This is then compared with long-term changes with the British archaeological record in order to understand in greater detail the changing patterns of climatic forcing and the major climatic transitions that were the background environmental drivers against which patterns of early human occupation occurred. These include the mid-Pleistocene revolution, the mid-Brunhes event, and changing patterns of isotopic substage complexity. Significantly, however, the SST record indicates that the Marine Oxygen Isotope Stage 15–13 interval was characterised by the most prolonged period of consistently warm conditions of the entire 1 Ma interval in the northeast Atlantic. This unique climatic period correlates with the first major proliferation of archaeological sites in northwest Europe. The article concludes by discussing the significance of these climatic shifts for our understanding of early human occupation in this region.